Five new species of Inosperma from China: Morphological characteristics, phylogenetic analyses, and toxin detection - Li, Sai-Nan; Xu, Fei; Long, Pan; Liu, Feng; Zhang, Ping; Fan, Yu-Guang; Chen, Zuo-Hong (Frontiers in Microbiology, 2022)
Many species of Inosperma cause neurotoxic poisoning in humans after consumption around the world. However, the toxic species of Inosperma and its toxin content remain unclear. In the present study, we proposed five new Inosperma species from China, namely, I. longisporum, I. nivalellum, I. sphaerobulbosum, I. squamulosobrunneum, I. squamulosohinnuleum. Morphological and molecular phylogenetic analyses based on three genes (ITS, nrLSU, rpb2) revealed that they are distinct species. A key to 17 species of Inosperma in China is provided. In addition, targeted screening for the most notorious mushroom neurotoxins, muscarine, psilocybin, ibotenic acid and muscimol, in these five new species was performed by using ultrahigh-performance liquid chromatography tandem mass spectrometry (UPLC–MS/MS). Our results show that the neurotoxin contents in these five species varied: I. sphaerobulbosum contains none of the tested neurotoxins; I. nivalellum is muscarine positive; I. longisporum and I. squamulosohinnuleum contain both ibotenic acid and muscimol, and I. squamulosobrunneum only contains muscimol; psilocybin was not detected in these five new species.